Biologi Predator Cheilomenes sexmaculata (Fabr.) (Coleoptera: Coccinellidae) pada Kutu Daun Macrosiphoniela sanborni Gilette (Homoptera: Aphididae) - CYCCU TOBING, MARYANI; BAKTI NASUTION, DARMA (AGRITROP, 2012)
A research was conducted at the screening house and laboratory of Department of Plant Pests and Diseases, University of North Sumatra, Medan, under room temperature of 20-30oC and relative humidity 78-94%. The objectives of this research were to study the morphological and biological characteristic. The results showed that egg, first, second, third and fourth larva instars, and pupae stages of C. sexmaculata were 2,70 ± 0.82; 1,60 ± 0.51; 2,30 ± 0.48; 3,10 ± 0.56; 4,50 ± 0,52 and 4,30 ± 0.48 days respectively. Fecundity was 136,20 ± 10.37 eggs, fertility 81,82 ± 8,17% and life cycle 52,40 ± 0.69 days. The female lived for 31,20 ± 2,69 days longer than male which were 30,00 ± 3,26 days. Rate reproduction (Ro) = 5 and intrinsic rate of increase (rm) = 0,067.
Keywords: biology, Cheilomenes sexmaculata, Macrosiphoniella sanborni